STUDY OF COASTAL SEAWATER INTRUSION OF TANGERANG DISTRICT AS A BASIS FOR SUSTAINABLE INDUSTRIAL AREA PLANNING - Utami, Ika Wahyu; Putri , Larasati Rizky; Najih , Muhammad (Komunitas Menulis dan Meneliti (Kolibi), 2024)
A decline in groundwater quality in the coastal part of Tangerang Regency, which directly borders the Java Sea, has been identified in recent years. This content analysis research examines the suitability of the coast of Tangerang Regency, especially the Kosambi sub-district, as an industrial area based on the RPIJM of the Tangerang Regency government. Groundwater quality and the impact of intrusion in the study area were analyzed based on secondary data obtained from the Groundwater and Subsidence Monitoring System of the Ministry of Energy and Mineral Resources at 15 water sample points. The parameters analyzed include physical, chemical and inorganic water parameters. The results obtained from the analysis of various parameters show that groundwater in the study area is polluted by seawater. The plan to develop an industrial area in the study area will certainly impact increasingly severe levels of intrusion in the study area if the plan does not pay attention to preserving groundwater resources.